Modifications on PVC films by ultrasound - Martins-Franchetti, S. M.; Domingos, R. N.; Trombini, R. C. (Elsevier B.V., 2002)
PVC films submitted to ultrasonic irradiation presented structural changes as probed by infrared measurements. These measurements showed some infrared bands alterations attributed to the increase concentration of some conformational isomers of PVC and the presence of some new species in the macromolecular matrix. (C) 2002 Elsevier B.V. B.V. All rights reserved.
Keywords: infrared; PVC films; ultrasound